Modeling of Excess‐3 to BCD code converter for nano system using quantum‐dot cellular automata technology. (15th August 2022) - Khan, Angshuman; Safoev, Nuriddin; Arya, Rajeev
Abstract: This work proposes a novel quantum‐dot cellular automata (QCA) layout for an Excess‐3 to BCD code converter for nano systems that is low in cell complexity. The suggested design uses a QCA clock‐phase‐based technique to evaluate integration with other complex circuits. The results obtained using the QCADesigner simulation tool demonstrate the superiority of the recommended layout over prior identical reverse counterpart designs by evaluating the cell numbers used, the space occupied, and the latency as design metrics. The suggested layout has a 56% decrease in occupied space and a 37.5% reduction in delay when compared to similar reverse counterpart scalable designs. In addition, the energy dissipation of the suggested structure was calculated and compared to previous comparable work (reverse equivalent) to confirm its reliability. The suggested circuit may be employed in bigger and more complicated circuits due to its advantage in numerous performance measurement parameters.